Comparison of in vivo and in situ detection of hippocampal metabolites in mouse brain using 1H‐MRS. (30th November 2020) - Hsu, Chao‐Hsiung; Lin, Stephen; Ho, Ai‐Chen; Johnson, T. Derek; Wang, Paul C.; Scafidi, Joseph; Tu, Tsang‐Wei
Abstract : The study of cerebral metabolites relies heavily on detection methods and sample preparation. Animal experiments in vivo require anesthetic agents that can alter brain metabolism, whereas ex vivo experiments demand appropriate fixation methods to preserve the tissue from rapid postmortem degradation. In this study, the metabolic profiles of mouse hippocampi using proton magnetic resonance spectroscopy ( 1 H‐MRS) were compared in vivo and in situ with or without focused beam microwave irradiation (FBMI) fixation. Ten major brain metabolites, including lactate (Lac), N‐acetylaspartate (NAA), total choline (tCho), myo‐inositol (mIns), glutamine (Gln), glutamate (Glu), aminobutyric acid (GABA), glutathione (GSH), total creatine (tCr) and taurine (Tau), were analyzed using LCModel. After FBMI fixation, the concentrations of Lac, tCho and mIns were comparable with those obtained in vivo under isoflurane, whereas other metabolites were significantly lower. Except for a decrease in NAA and an increase in Tau, all the other metabolites remained stable over 41 hours in FBMI‐fixed brains. Without FBMI, the concentrations of mIns (before 2 hours), tCho and GABA were close to those measured in vivo. However, higher Lac ( P < .01) and lower NAA, Gln, Glu, GSH, tCr and Tau were observed ( P < .01). NAA, Gln, Glu, GSH, tCr and Tau exhibited good temporal stability for at least 20 hours in the unfixed brain, whereas a linear increase of tCho, mIns and GABA was observed. Possible mechanisms of postmortem degradation are discussed. Our results indicate that a proper fixation method is required for in situ detection depending on the targeted metabolites of specific interests in the brain. Abstract : The mouse hippocampal metabolites after direct decapitation (no fixation), by focused beam microwave irradiation (FBMI) fixation over 41 hours, and in vivo condition under isoflurane anesthesia, were analyzed from 1 H‐MRS. Metabolites showing various time curves under different conditions indicate that a proper fixation method is required depending on the targeted metabolites of specific interest.